2013
DOI: 10.1371/journal.pone.0079710
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with Insulin Analog X10 and IGF-1 Increases Growth of Colon Cancer Allografts

Abstract: Obesity and type 2 diabetes are associated with an increased risk for development of certain forms of cancer, including colon cancer. The publication of highly controversial epidemiological studies in 2009 raised the possibility that use of the insulin analog glargine increases this risk further. However, it is not clear how mitogenic effects of insulin and insulin analogs measured in vitro correlate with tumor growth-promoting effects in vivo. The aim of this study was to examine possible growth-promoting eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 44 publications
1
27
1
2
Order By: Relevance
“…It has been reported that treatment with IGF-I significantly increased the growth of MC38 cell allograft in mice with diet induced obesity [41]. Similarly, it was found that IGF increases cell proliferation in pancreatic tumors [42] and activation of the IGFR-I by IGF-I is associated with the risk and progression of many types of cancer [43].…”
Section: Discussionmentioning
confidence: 95%
“…It has been reported that treatment with IGF-I significantly increased the growth of MC38 cell allograft in mice with diet induced obesity [41]. Similarly, it was found that IGF increases cell proliferation in pancreatic tumors [42] and activation of the IGFR-I by IGF-I is associated with the risk and progression of many types of cancer [43].…”
Section: Discussionmentioning
confidence: 95%
“…5 High plasma insulin results in increased hepatic production of IGF-1, which has a central driving role in cell proliferation and differentiation, protecting against apoptosis. 24 Over expression of IGF-1 and IGF-1 receptor was associated with an increased risk of prostate, cervical, ovarian, breast and colon cancers in clinical studies, 5,25 and with increased tumor growth in vitro 26 and in animal models. 27 Furthermore, there is growing understanding of the role of metabolic dysregulation and reliance on aerobic glycolysis in RCC pathogenesis, known as the Warburg effect.…”
Section: Discussionmentioning
confidence: 99%
“…One such analog that is not in clinical use is known as AspB10, as it has an amino acid substitution of aspartic acid in place of histidine at position 10 on the B chain of insulin. This insulin analog was found to induce spontaneous mammary tumors in rats and has subsequently been shown to be mitogenic in human breast cancer cells in vitro (135) and in animal models of breast and colon cancer (59,85). Human registry studies and retrospective cohort studies published in 2011-2012 reported that other insulin analogs may increase the risk of certain cancers, including breast cancer (74,165,179).…”
Section: Insulin Therapymentioning
confidence: 99%